2008
DOI: 10.1002/cncr.23979
|View full text |Cite
|
Sign up to set email alerts
|

Early versus late intensification for patients with high‐risk Hodgkin lymphoma—3 Cycles of intensive chemotherapy plus low‐dose lymph node radiation therapy versus 4 cycles of combined doxorubicin, bleomycin, vinblastine, and dacarbazine plus myeloablative chemotherapy with autologous stem cell transplantation

Abstract: BACKGROUND. The 5‐year freedom from treatment failure (FFTF) rate, with treatment failure defined as the lack of post‐treatment complete remission (CR), recurrence, or death, ranges from 60% to 70% after 6 to 8 cycles of combined doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD), which is the reference treatment for patients with advanced Hodgkin lymphoma (HL). In this randomized, phase 2 study, the authors tested 2 intensive chemotherapy regimens in 158 patients with clinical stage (CS) IIB through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…HCT was given for the treatment of lymphoproliferative diseases (16 trials), [13][14][15][16][17][18][19][20][21][22][23][24]29,30,32 solid malignancies (16 trials) 25,27,28,31,[33][34][35][36][37][38][39][40][41][42][43][44] and plasma cell disorders [10][11][12]26 (4 trials). Two trials used purged autografts as the graft source.…”
Section: Resultsmentioning
confidence: 99%
“…HCT was given for the treatment of lymphoproliferative diseases (16 trials), [13][14][15][16][17][18][19][20][21][22][23][24]29,30,32 solid malignancies (16 trials) 25,27,28,31,[33][34][35][36][37][38][39][40][41][42][43][44] and plasma cell disorders [10][11][12]26 (4 trials). Two trials used purged autografts as the graft source.…”
Section: Resultsmentioning
confidence: 99%
“…17 This study examined an early intensive nonmyeloablative chemotherapy (VABEM: vindesine, doxorubicin, carmustine, etoposide and methylprednisolone) and ABVD for 4 cycles followed by delayed myeloablative intensification (BEAM high-dose therapy and ASCT). The authors reported the results of 158 patients (82 in the VABEM arm, 76 in the ASCT arm) and compared FFTF (primary endpoint) and OS in a randomized phase II trial.…”
Section: Consolidation Post Primary Chemotherapymentioning
confidence: 99%
“…Although the definition of "high-risk" has varied and included only elements of the IPS, randomized clinical trials have concluded no benefit for early intensification with autologous stem cell transplantation in patients with unfavorable disease responding to anthracycline-based therapy. [28][29][30] The pertinent question becomes how to identify up front the ϳ 20% or so of cases that may not do well with standard approaches. Emerging data support that a negative PET may be predictive after 2 cycles of chemotherapy.…”
Section: Can We Adapt Therapy Based On Clinical or Biological Risk Famentioning
confidence: 99%